Highly active sunlight-driven CO2 methanation catalyst: Design of the interfacial structure. (1st March 2023) - Yuan, Shaoyu; Ma, Peipei; Yang, Yushan; Shen, Xinlei; Pan, Heli; Li, Zixuan; Li, Yaguang; Gao, Yongjun
Abstract: A kind of nickel catalyst supported on the defect-rich ZrO 2 (5Ni/ZrO 2 -0.5R) was developed, which exhibited 66 ∼ 70% of CO 2 conversion accompanied with more than 99% CH 4 selectivity in the range of 300 ∼ 380 °C. Thus, the green and sustainable CO 2 methanation over 5Ni/ZrO 2 -0.5R can be achieved smoothly in a photo-thermal transform tube that can provide temperature range of 300 ∼ 400 °C under sun. A combination of control experiments, in-situ spectroscopy analyses and characterizations provides an insight into the active sites at the interface between nickel and oxygen vacancy(O v )-rich ZrO 2 . The presence of sodium and oxygen vacancies promotes the dissociative adsorption of CO 2 so that change the mechanism of CO 2 methanation from formate-hydrogenation pathway into CO-hydrogenation pathway. Further theoretical calculations indicate that the Zr 4 + -O v structures leads to significantly improved Ni dispersion and the Na + -O v -Ni sites drive the CO 2 methanation through a CO-hydrogenation mechanism. Graphical abstract: Highlights: High-temperature processing strategy with NaBH 4 introduces sodium and oxygen vacancy to ZrO 2 . The catalytic CO 2 methanation over Ni/ZrO 2 was achieved under solar irradiation. The Na + -O v -Ni interface promotes CO 2 dissociative adsorption and causes the CO-hydrogenation pathway for CO 2 methanation.